2017
DOI: 10.18632/oncotarget.21644
|View full text |Cite
|
Sign up to set email alerts
|

The clinical use of circulating microRNAs as non-invasive diagnostic biomarkers for lung cancers

Abstract: Many studies have investigated the diagnostic role of circulating microRNAs (miRNAs) in patients with lung cancer; however, the results still remain inconclusive. An updated system review and meta-analysis was necessary to give a comprehensive evaluation of diagnostic role of circulating miRNAs in lung cancer. Eligible studies were searched in electronical databases. The sensitivity and specificity were used to plot the summary receiver operator characteristic (SROC) curve and calculate the area under the curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 86 publications
(83 reference statements)
1
32
0
Order By: Relevance
“…Moreover, the same authors had previously analyzed the expression profile of serum miRNAs in a large cohort of 391 advanced stage (III and IV stage) patients, identifying a 17-miRNA risk score. Notably, patients with a high risk miRNA profile in serum showed a 2.5-fold increased risk of death compared with those with a low risk score (95% CI: 1.8-3.4; p = 1.1 × 10 −7 ) [66]. Very recently, a similar study including more than 500 individuals with metastatic lung cancer, identified five serum miRNAs (miR-191, miR-28-3p, miR-145, miR-328, and miR-18a) significantly associated with the 3-year overall survival [68].…”
Section: Circulating Mirnasmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the same authors had previously analyzed the expression profile of serum miRNAs in a large cohort of 391 advanced stage (III and IV stage) patients, identifying a 17-miRNA risk score. Notably, patients with a high risk miRNA profile in serum showed a 2.5-fold increased risk of death compared with those with a low risk score (95% CI: 1.8-3.4; p = 1.1 × 10 −7 ) [66]. Very recently, a similar study including more than 500 individuals with metastatic lung cancer, identified five serum miRNAs (miR-191, miR-28-3p, miR-145, miR-328, and miR-18a) significantly associated with the 3-year overall survival [68].…”
Section: Circulating Mirnasmentioning
confidence: 98%
“…Recently, a meta-analysis, including almost 14,000 individuals (6919 patients and 7064 controls) from 134 studies has shown that the circulating miRNAs had an optimal diagnostic accuracy (area under the curve AUC: 0.90) with high sensitivity (82%) and specificity (81%). The pooled analysis identified a 4-miRNA panel (miR-21-5p, miR-223-3p, miR-155-5p, and miR-126-3p) as a potential biomarker for lung cancer screening [66]. The authors also reported serum samples as a more suitable source of tumor derived miRNAs than plasma samples.…”
Section: Circulating Mirnasmentioning
confidence: 98%
“…Circulating microRNAs in blood have been demonstrated as promising biomarkers for lung cancer diagnosis. Results from recent metaanalyses of more than 100 studies showed that circulating microRNAs, such as miR-21, miR-155 and miR-126, have good diagnostic performance in lung cancer with both sensitivity and specificity above 0.8 (Yang et al, 2017;Yu et al, 2018Yu et al, , 2019. And the diagnostic accuracy can be further improved when a panel of microRNAs are used as the combined biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating microRNAs carried by exosomes have been demonstrated as potential biomarkers for lung cancer. For example, a panel of circulating microRNAs including miR-21, miR-223, miR-155, and miR-126 were identified as potent biomarkers for lung cancer in a recent meta-analysis study involving 6919 lung cancer patients and 7064 controls (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Using the above panel of miRNAs with high sensitivity, followed by the second panel with high specificity in screening for stage I-II NSCLC, they obtained a pooled specificity of 93.4% and a pooled sensitivity of 91.6% [119]. However, these results, among those from other studies [120,121], need proper validation before they can prove their benefit. In a recent study, miR-223 has been validated as an effective and reproducible serum biomarker of early stage NSCLC by using digital-droplet PCR technology [122].…”
Section: Circulating Noncoding Rnasmentioning
confidence: 95%